Higher serum phosphorus is associated with catabolic/anabolic imbalance in heart failure. Issue 4 (22nd April 2015) - Rozentryt, Piotr; Niedziela, Jacek T.; Hudzik, Bartosz; Lekston, Andrzej; Doehner, Wolfram; Jankowska, Ewa A.; Nowak, Jolanta; von Haehling, Stephan; Partyka, Robert; Rywik, Tomasz; Anker, Stefan D.; Ponikowski, Piotr; et al.
Abstract: Background: A higher serum phosphate level is associated with worse outcome. Energy‐demanding intracellular transport of phosphate is needed to secure anion bioavailability. In heart failure (HF), energy starvation may modify intracellular and serum levels of phosphate. We analysed determinants of serum phosphates in HF and assessed if catabolic/anabolic balance (CAB) was associated with elevation of serum phosphate. Methods: We retrospectively reviewed data from 1029 stable patients with HF and have calculated negative (loss) and positive (gain) components of weight change from the onset of HF till index date. The algebraic sum of these components was taken as CAB. The univariate and multivariable predictors of serum phosphorus were calculated. In quintiles of CAB, we have estimated odds ratios for serum phosphorus above levels previously identified to increase risk of mortality. As a reference, we have selected a CAB quintile with similar loss and gain. Results: Apart from sex, age, and kidney function, we identified serum sodium, N‐terminal fragment of pro‐brain‐type natriuretic peptide, and CAB as independent predictors of serum phosphorus. The odds for serum phosphorus above thresholds found in literature to increase risk were highest in more catabolic patients. In most catabolic quintile relative to neutral balance, the odds across selected phosphorus thresholds rose, gradually peaking at 1.30 mmol/L with a value of 3.29 (95% confidence interval: 2.00–5.40, P < 0.0001) in an unadjusted analysis and 2.55 (95% confidence interval: 1.38–2.72, P = 0.002) in a fully adjusted model. Conclusions: Metabolic status is an independent determinant of serum phosphorus in HF. Higher catabolism is associated with serum phosphorus above mortality risk‐increasing thresholds.